Associations between different bilirubin subtypes and diabetic microvascular complications in middle-aged and elderly individuals. (July 2020) - Wan, Heng; Zhu, Hui; Wang, Yuying; Zhang, Kun; Chen, Yi; Fang, Sijie; Xia, Fangzhen; Wang, Ningjian; Zhang, Wen; Lu, Yingli
Aims: Some studies have reported associations between bilirubin and diabetic microvascular complications. However, these studies focused only on total bilirubin (TBIL) without distinguishing different bilirubin subtypes. In this study, we aimed to investigate the associations of TBIL, direct bilirubin (DBIL) and indirect bilirubin (IBIL) levels with albuminuria/creatinine ratio (ACR) and the prevalence of diabetic retinopathy (DR) among diabetic adults. Methods: We analyzed 4368 individuals out of 4813 diabetic participants enrolled from seven communities in 2018 in a cross-sectional study. Participants underwent several checkups, including the measurement of anthropometric parameters, blood pressure, glucose, lipid profile, TBIL, DBIL, IBIL and ACR. DR was detected by high-quality fundus photographs and was remotely read by ophthalmologists. Results: Compared with the first quartile of DBIL, participants in the fourth quartile had a lower prevalence of high ACR (odds ratio (OR) 0.76; 95% confidence interval (CI) 0.59, 0.99) ( p for trend < 0.05). Neither TBIL nor IBIL was associated with the prevalence of high ACR. In DR, higher DBIL and TBIL by one standard deviation was associated with a 19% (OR 0.81; 95% CI 0.69, 0.94) and a 12% (OR 0.88; 95% CI 0.78, 0.99) lower frequency of DR, respectively (both p for trend < 0.05). However, IBIL was not associated with the prevalence of DR. These associations were adjusted for potential confounding factors. Conclusion: DBIL had a stronger association with high ACR and DR than TBIL or IBIL did in diabetic adults. The effect of DBIL on diabetic complications should be noted and investigated in further studies.